Transcriptomic analysis identifies lactoferrin-induced quiescent circuits in neonatal macrophages - Eigenschink, Michael; Wessely, Isabelle; Dijmarescu, Marco; Förster-Waldl, Elisabeth; Farr, Alex; Kiss, Herbert; Berger, Angelika; Wisgrill, Lukas (Frontiers in Immunology, 2023)
Introduction Upon birth, a hitherto naïve immune system is confronted with a plethora of microbial antigens due to intestinal bacterial colonization. To prevent excessive inflammation and disruption of the epithelial barrier, physiological mechanisms must promote immune-anergy within the neonatal gut. As high concentrations of human lactoferrin (hLF), a transferrin glycoprotein shown to modulate macrophage function, are frequently encountered in colostrum, its direct interaction with intestinal macrophages may satisfy this physiological need. Thus, the primary objective of this study was to investigate transcriptional changes induced by human lactoferrin in neonatal monocyte-derived macrophages. Methods Cord blood-derived monocytes were differentiated with M-CSF in presence or absence of 500 µg/mL hLF for 7 days and afterwards stimulated with 1 ng/mL LPS or left untreated. RNA was then isolated and subjected to microarray analysis. Results Differentiation of cord blood-derived monocytes in presence of hLF induced a distinct transcriptional program defined by cell cycle arrest in the G2/M phase, induction of IL-4/IL-13-like signaling, altered extracellular matrix interaction, and enhanced propensity for cell-cell interaction. Moreover, near-complete abrogation of transcriptional changes induced by TLR4 engagement with LPS was observed in hLF-treated samples. Discussion The global transition towards an M2-like homeostatic phenotype and the acquisition of quiescence elegantly demonstrate the ontogenetical relevance of hLF in attenuating pro-inflammatory signaling within the developing neonatal intestine. The marked anergy towards proinflammatory stimuli such as LPS further underlines the glycoprotein’s potential therapeutic relevance.